P2Y2 Receptor Induces L. amazonensis Infection Control in a Mechanism Dependent on Caspase-1 Activation and IL-1β Secretion - Maria Luiza Thorstenberg; Monique Daiane Andrade Martins; Vanessa Figliuolo; Claudia Lucia Martins Silva; Luiz Eduardo Baggio Savio; Robson Coutinho-Silva (Mediators of Inflammation)
Leishmaniasis is a neglected tropical disease caused by an intracellular parasite of the genus Leishmania. Damage-associated molecular patterns (DAMPs) such as UTP and ATP are released from infected cells and, once in the extracellular medium, activate P2 purinergic receptors. P2Y2 and P2X7 receptors cooperate to control Leishmania amazonensis infection. NLRP3 inflammasome activation and IL-1β release resulting from P2X7 activation are important for outcomes of L. amazonensis infection. The cytokine IL-1β is required for the control of intracellular parasites. In the present study, we investigated the involvement of the P2Y2 receptor in the activation of NLRP3 inflammasome elements (caspase-1 and 11) and IL-1β secretion during L. amazonensis infection in peritoneal macrophages as well as in a murine model of cutaneous leishmaniasis. We found that 2-thio-UTP (a selective P2Y2 agonist) reduced parasite load in L. amazonensis-infected murine macrophages and in the footpads and lymph nodes of infected mice. The antiparasitic effects triggered by P2Y2 activation were not observed when cells were pretreated with a caspase-1 inhibitor (Z-YVAD-FMK) or in macrophages from caspase-1/11 knockout mice (CASP-1,11−/−). We also found that UTP treatment induced IL-1β secretion in wild-type (WT) infected macrophages but not in cells from CASP-1,11−/− mice, suggesting that caspase-1 activation by UTP triggers IL-1β secretion in L. amazonensis-infected macrophages. Infected cells pretreated with IL-1R antagonist did not show reduced parasitic load after UTP and ATP treatment. Our in vivo experiments also showed that intralesional UTP treatment reduced both parasite load (in the footpads and popliteal lymph nodes) and lesion size in wild-type (WT) and CASP-11−/− but not in CASP-1,11−/− mice. Taken together, our findings suggest that P2Y2R activation induces CASP-1 activation and IL-1β secretion during L. amazonensis infection. IL-1β/IL-1R signaling is crucial for P2Y2R-mediated protective immune response in an experimental model of cutaneous leishmaniasis.